A qualitative study on user acceptance of a home-based stroke telerehabilitation system. Issue 2 (17th February 2020) - Chen, Yu; Chen, Yunan; Zheng, Kai; Dodakian, Lucy; See, Jill; Zhou, Robert; Chiu, Nina; Augsburger, Renee; McKenzie, Alison; Cramer, Steven C.
ABSTRACT: Objective : This paper reports a qualitative study of a home-based stroke telerehabilitation system. The telerehabilitation system delivers treatment sessions in the form of daily guided rehabilitation games, exercises, and stroke education in the patient's home. The aims of the current report are to investigate patient perceived benefits of and barriers to using the telerehabilitation system at home. Methods : We used a qualitative study design that involved in-depth semi-structured interviews with 13 participants who were patients in the subacute phase after stroke and had completed a six-week intervention using the home-based telerehabilitation system. Thematic analysis was conducted to analyze the data. Results : Participants mostly reported positive experiences with the telerehabilitation system. Benefits included observed improvements in limb functions, cognitive abilities, and emotional well-being. They also perceived the system easy to use due to the engaging experience and the convenience of conducting sessions at home. Meanwhile, participants pointed out the importance of considering technical support and physical environment at home. Further, family members' support helped them sustain in their rehabilitation. Finally, adjusting difficulty levels and visualizing patients' rehabilitation progress might help them in continued use of the telerehabilitation system. Conclusion : Telerehabilitation systems can be used as an efficient and user-friendly tool to deliver home-based stroke rehabilitation that enhance patients' physical recovery and mental and social-emotional wellbeing. Such systems need to be designed to offer engaging experience, display of recovery progress, and flexibility of schedule and location, with consideration of facilitating and social factors.